2014 IEEE 16th Conference on Business Informatics 2014
DOI: 10.1109/cbi.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Towards Controlling Lawful States and Events in Business Process Models

Abstract: In enterprises it is important to control whether unlawful events occur or business objects are in unlawful states during business process execution. Existing modelling methods such as BPMN and ArchiMate do not to a full extent support description of conceivable and lawful state and event spaces that can affect execution of the process. This gap jeopardizes compliance of business process models with external and internal regulations. This paper proposes a theoretical solution for closing the gap between busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The previous research [23] has shown the gap between business process models and state spaces of structural elements in business process models. In this paper mainly BPMN is considered as a notation for business processes modeling and ArchiMateas a language for enterprise architecture modeling due to reasons described in [23].…”
Section: Bww Based Linkage Between Enterprise Architecture and Businementioning
confidence: 99%
See 1 more Smart Citation
“…The previous research [23] has shown the gap between business process models and state spaces of structural elements in business process models. In this paper mainly BPMN is considered as a notation for business processes modeling and ArchiMateas a language for enterprise architecture modeling due to reasons described in [23].…”
Section: Bww Based Linkage Between Enterprise Architecture and Businementioning
confidence: 99%
“…In this paper mainly BPMN is considered as a notation for business processes modeling and ArchiMateas a language for enterprise architecture modeling due to reasons described in [23]. Existing modelling languages BPMN and ArchiMate lack elements for capturing states of structural elements [23].…”
Section: Bww Based Linkage Between Enterprise Architecture and Businementioning
confidence: 99%
“…In [1] authors investigate the use of temporal deontic assignments on activities as a means to declaratively capture the control-flow semantics that reside in business regulations and business policies. In object-oriented paradigm, state machines are extensively used for representation of states of objects [21]. In [22] the authors propose logic based formalism for describing the semantics of business contracts and the semantics of compliance checking procedures and close the gap between business processes and business contracts.…”
Section: Related Workmentioning
confidence: 99%
“…According to the approach, the BWW model of the policy can be represented in a formal way, e.g., as XML document, see Code Fragment 1 of the XML code below. The next step of the approach is to construct a BWW model from the existing BPMN process model based on the BPMN-BWW mapping presented in [17] and [21]. A fragment of the existing publishing business process BPMN model is depicted in Figure 2.…”
Section: Explicitly Definingmentioning
confidence: 99%
See 1 more Smart Citation